Adsorption removal of copper-containing wastewater on yazuv sulfur mine bentonite - Петрова, Маріанна Анатоліївна; Войтович, Мар’яна Олегівна (Eastern-European Journal of Enterprise Technologies, 2014)
The adsorption properties of bentonite clay of Yaziv mine (Lviv district, Ukraine) was investigated in the process of copper removal. Water contamination by copper originates from industrial wastewater discharge, thus effective methods for copper removal are required. Copper adsorption was effective in wide range of concentrations; the adsorbent saturation by copper ions did not take place. The assay boundary adsorption capacity was 31 mg/g. The kinetic characteristics of the adsorbent were defined and the time for copper removal did not exceed 2 hours. The pH range for the effective adsorption was determined, namely pH>4. The kinetic models were applied for the experimental data, namely pseudo-first, pseudo-second order, intraparticle diffusion, Bangham and Ritchie models. The process followed the pseudo-second order model, thus it was found to be limited by the chemical reaction between copper and functional groups of bentonite. When copper removal from solutions with high concentrations of potassium (up to 0.1M) was performed, the insignificant adsorption retardation was observed. This confirmed the activity of functional adsorption sites selective for copper during adsorption process. The combination of high capacity and favourable kinetic characteristics, along with the selectivity, confirmed the prospective for bentonite application in waste water treatment technologies.